Ennui - Edgeworth, Maria (Saga Egmont, 2022)
Lord Glenthorn is bored and lacking oomph. But before you feel sorry for him, it is worth knowing that he has a pile of money, a grand title, estates in England and Ireland and no stress. That is until he finds out he is not Lord Glenthorn, the Anglo-Irish earl. He is in fact the peasant Christy O\'Donoghoe, which is a fly in the ointment for his efforts to provide for the woman he loves. At the same time, he gets caught up in the violent Irish Rebellion of 1798. Can he shake off the ennui, become a self-made man and win the hand of his love? Those who enjoy Jane Austen\'s novels, including \'Persuasion\', \'Sense and Sensibility\', and \'Pride and Prejudice\', will love \'Ennui\'. Like Austen, Maria Edgeworth has a gift for gently exposing the hypocrisy and accidental comedy of Britain\'s 19th century upper-middle class. First published in 1809, \'Ennui\' is a didactic novel, which means it aims to teach the reader a moral lesson - like \'Aesop\'s Fables\'. The Irish writer Maria Edgeworth (1768-1849) was highly regarded in her day as a pioneer of early 19th century fiction and children\'s literature. A friend of the novelist Sir Walter Scott (\'Ivanhoe\', \'Rob Roy\'), she was active and vocal about political and estate reform. Today, she is rather underappreciated - and overshadowed - by other 19th century satirical novelists like Jane Austen and Anthony Trollope. A prolific writer, Edgeworth\'s best-known works include \'Ennui\', \'The Dun\' and \'Belinda\', which was controversial in its day for featuring inter-racial marriage.